A criança-consumidora: a genealogia de um fenômeno contemporâneo 1950-2000 - Rossi, Eliane Pimenta Braga (2007)
This work has as aim the discussion about the consumer child s historical process formation. The problems resulting from this issue include a wider perception about the social relationships within a symbolic system guided by references roused by social experiences during the second half of the last century. The historical construction of the contemporary subject remits to their own childhood remeaning. This re-meaning is perceptible at the changing of the child s representation present at goods publicity designed to their use, as well as its usage in goods campaigns which are not designed to them. Through publicity, it is possible to notice these changes due to the advertisers effort in creating their campaigns having as source the social imaginary and the current representations in society. The creation of meanings, interposed by specific values on each social segment, starts, thus, to suffer a remarkable influence of an aspect which was previously restricted to commercial trades, the marketing. Publicity and commercial advertisements, which used to sell goods and/or a necessity, have acquired the status of belonging to a life style. Therefore, the consumer child is figures as a sui generis subject due to their condition of non-belonging to the world of work and, consequently, not having an income. Such paradox does not constitute a problem to the position as a consumer, because, as one, they became demanding, voracious and extremely sensitive to the seductions immanent to publicity. This significant changing ended up in re-meaning not only the childhood but also figuring it as a reference to the other phases of life.